URGENSI BADAN USAHA MILIK DESA (BUMDES) DALAM PEMBANGUN PEREKONOMIAN DESA - ridlwan, zulkarnain (Lampung University, 2014)
The purpose of this paper is to describe the importance of village-owned enterprises and the management in the interests of rural communities. Referring to the legislation governing the rural , particularly Law No. 6 of 2014, it can be concluded that the village-owned enterprises is a village economic institution that has an important role in the welfare of the community, the village, and the village government. A professional governance that refers to the guidelines in the formation of village-owned enterprises based on legislation is a prerequisite of village-owned enterprises goes properly. Thus the economic activities of village-owned enterprises should ideally be part of efforts to increase local and regional economies within the scope of the national economy.Â Keywords: Urgency of Village-Owned Enterprises, Formation and Management.